Tinjauan Kesesuaian Fasilitas Halte Bus Trans Metro Pekanbaru Koridor 3 Terhadap Standar Dirjend Perhubungan Darat Tahun 2012 Dan Wahana Tata Nugraha Tahun 2010 - Diva Melissa; Yosi Alwinda; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One most important service aspect of Trans Metro Pekanbaru is a bus stop. Trans Metro Pekanbaru Bus Stop is a place where passenges get on and off from the Bus as well as a place to transit from one to another place orderly, smoothly, safely, and comfortable. Thecondition of bus stop must suit the well-construct building that it can be comfort and be a shelter from the sun and the rain. The condition of facility at coridor 3 is still deficient, henceit needs to observe the suitability of facility according to Standard Directorate General of Land Transportation 2012 and Wahana Tata Nugraha 2010. The result of judgement for busstop condition at corridor 3 showed it was included into deficient category since the weight of all judgement were 40%. Percentage result of bus stop facility according to weight of judgement was in efficient category of 3,77% for 2 bus stops, sufficient category of 35.19%for 19 bus stops, deficient cateogry of 46.30% for 25 bus stops and less deficient category of 13.21% for 7 bus stops. TMP bus stop at coridor 3 is type 1 witb average weight of judgement was 26.71% and was included into deficient category, type 2 with 11% weight of judgement and was less deficient, and type 3 with 30% weight of judgement and wasdeficient.Keywords: Bus stop, Condition, TMP (Trans Metro Pekanbaru), Corridor, WTN (Wahana Tata Nugraha)